Diagnoza partycypacyjna a rewitalizacja przypadek gorzowskiego Kwadratu = Participatory diagnosis and revitatlization. The case of Kwadrat in Gorzów Wielkopolski - Frątczak-Müller, Joanna; Łukowiak, Anita (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Revitalization is a social venture which aims to bring degraded areas out of crisis. The article presents participatory diagnosis as a method worth implementing in revitalization processes. The discussion is based on the analysis of the revitalization process of Plac Nieznanego Żołnierza (a square commemorating unknown soldiers, commonly referred to as Kwadrat) carried out in GorzówWielkopolski between 2017 and 2018. For this purpose, participatory analysis techniques are used. Based on this example, the authors present the goals, tasks, and possible effects of the process. Also, important relations between the public, private and civic sectors, which create a local network of co-operation, are discussed. The authors emphasize the importance of resident participation as a key factor leading to changes in the revitalization process.
Keywords: rewitalizacja; partycypacja społeczna; diagnoza partycypacyjna; program rewitalizacyjny; revitalization; social participation; participatory diagnosis; program